'Animating' the narrative in abstract comics. Issue 2 (1st October 2013) - Davies, Paul Fisher
How can one read an abstract graphic narrative? Under what conditions do we cease to view a set of images as static representations, or as marks on paper existing for their own sake, and begin to read them as the story of a changing world in motion, or even invest them with impetus, emotions and desires? In this article I will explore the ways in which readers can make sense of abstract comics. The notion of an abstract graphic narrative seems to be a contradiction in terms: how can something be non-representational, and also be a narrative, a category which seems to presuppose representations of characters, settings and events? When confronted with these visual texts, readers will have to seek out and create such 'actants' and 'existents' from the material abstract comics offer, if the text is to warrant its status as narrative. The article will use a number of exemplar stories from Andrei Molotiu's 2009 collection Abstract Comics to explore the process of reading these image texts. It will use ideas from narratology and philosophy of consciousness to help outline some of the ways we can 'animate' the static images we see across the sequence of panels, in which we recognize and reconstitute persistent entities, bringing a narrative life to the apparently inert marks on the comics page. I will explore the limits of readers' ability to apply this process and comment on its relevance to more mainstream graphic narrative in general.